2019
DOI: 10.1088/1742-6596/1375/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Technology transfer program for SMEs in Indonesia

Abstract: Technology transfer is a way to improve technology capability, especially for Small to Medium Enterprises (SMEs) in Emerging Economies such as in Indonesia. SMEs are often thought to have insufficient resources for advancing their in-house technology development. Therefore, SMEs need technology transfer programs to increase their technology capability. Government, Business, Universities have been involved in technology transfer program in this country. Using data from about 200 Javanese metal-based SMEs, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…While they have not been sufficiently ready to deal with the issue, global influence will undoubtedly bring an impact on MSMEs ( Tanev, 2017 ). Therefore, it is necessary to develop micro and MSE businesses' on an ongoing basis to make them ready to compete globally ( Handoko et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…While they have not been sufficiently ready to deal with the issue, global influence will undoubtedly bring an impact on MSMEs ( Tanev, 2017 ). Therefore, it is necessary to develop micro and MSE businesses' on an ongoing basis to make them ready to compete globally ( Handoko et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…An energy efficiency intention is a form of desire to be wise and efficient when consuming energy. Previous research found that energy efficiency intention has a positive and significant effect on energy-saving behaviour [42,43,44]; the higher the intention, the higher the saving energy behaviour [45,46]. This has informed analysis of the millennial generation's energy efficiency intention on their behaviour in an eco-friendly home and the formulation of the hypothesis H5: H5: Energy efficiency intention has a positive and significant effect on the millennial energy efficiency behaviour in an eco-friendly home.…”
Section: Energy Efficiency Intention and Behaviourmentioning
confidence: 97%
“…Consequently, companies need to develop environmentally sound strategies and innovations in the pallet procurement unit to meet distribution needs. Knowledge and technology regarding the green approach will help companies to be aware of environmentally friendly manufacturing through assisting the organization in improving knowledge and technology capability ( Wijayaningtyas et al., 2019 , 2020 ; Putri et al., 2020 ; Hulukati et al., 2020 ; Handoko et al., 2014 , 2016 , 2017 , 2019 ; Hidayat et al., 2018 ). This research is a case study of pallet shortage in the pulp and paper industry in Indonesia.…”
Section: Introductionmentioning
confidence: 99%